The influence of carbon on the microstructure and wear resistance of alumina. Issue 8 (16th April 2021) - Marder, Rachel; Ghosh, Priyadarshini; Reimanis, Ivar; Kaplan, Wayne D.
Abstract: The influence of carbon as a dopant on grain growth and wear resistance of polycrystalline alumina was evaluated. Carbon was introduced into alumina by sintering in a carbon‐rich environment (graphite furnace under flowing He), and/or by residual carbon from organic binders used during the green body consolidation process. Samples were sintered at 1600°C for 2 h. Doping alumina with carbon resulted in a reduced grain size after sintering, correlated to solute‐drag, and graphite particle‐drag for high concentrations of carbon ( 3 wt.%). The material response to abrasive wear was quantified by measuring the sample area cut for a defined time using a diamond wafering saw, as a function of grain size and carbon content. Sintering alumina with carbon resulted in a significant increase in wear resistance, as a result of the reduced grain size.